O papel do consumo de cacau na cardioproteção - Peres, Gabriela Baisch (Universidade do Vale do Rio dos Sinos, 2011)
The chronic diseases, including neoplasms, respiratory diseases, diabetes mellitus and cardiovascular disease, are a serious public health problem. Cardiovascular diseases are the first cause of death in almost all parts of the world as well as Brazil. These diseases are multifactorial in origin and are caused by risk factors that can or can’t be capable of being modified. Smoking, physical inactivity, inadequated diet, obesity, excessive consumption of alcoholic beverages, etc, are factors capable to intervene. The incorporation foods with functional properties of the diet as flavonoids natural antioxidants has been proposed in order to assist the reduction of modifiable risk factors. Cocoa is among the foods rich in flavonoids. The purpose of this study was to review the cardioprotective effect of cocoa consumption in humans. The results indicate that cocoa has effect anti-inflammatory, antiplatelet, antihypertensive, besides improving the bioavailability of nitric oxide, preventing endothelial dysfunction, and lipid profile. The conclusion of this study is that introduction of cocoa in the diet is an easy modification of joining and can be a promising approach to reduce risk of cardiovascular events.
Keywords: Cacau e antioxidantes; Antioxidantes polifenóis; Flavonóides; Chocolate escuro; Doenças cardiovasculares; Cocoa and antioxidants; Antioxidants polyphenols; Flavonoids; Dark chocolate; Cardiovascular disease